2019
DOI: 10.20473/ijosh.v8i2.2019.150-157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Work Climate and Physical Workload with Work-Related Fatigue

Abstract: Introduction: Work-related fatigue is a common problem in the workplace that must be solved because it has an impact on the occurrence of workplace accidents, reduces productivity and affects workers’ health. A survey conducted by the National Safety Council on 2010 workers in 2017 stated that 69% of them experienced work-related fatigue and 13% of them could be attributed to workplace accidents. Other studies conducted by O'Neill and Panuwatwanich in 2013 stated the loss that could arise due to work-related f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
4
0
5
Order By: Relevance
“…According to the Bureau of Labor Statistics (2019), individuals who work more than 40 hours per week or 8 hours per day may experience fatigue. Several past studies showed that physical workload is positively related to work fatigue in employees (Mustofani & Dwiyanti, 2019;Mulia, 2019;Ansori, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Bureau of Labor Statistics (2019), individuals who work more than 40 hours per week or 8 hours per day may experience fatigue. Several past studies showed that physical workload is positively related to work fatigue in employees (Mustofani & Dwiyanti, 2019;Mulia, 2019;Ansori, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The unit of measurement was milliseconds (ms). The measurement results were further classified according to several criteria according to Mustofani and Dwiyanti (2019) and Maurits (2010): criterion for normal work fatigue with a reaction time of 150.0-239.0 ms, criterion for mild work fatigue with a reaction time of 240.0 -< 409.0 ms, criterion for moderate work fatigue with a reaction time of 410.0-580.0 ms, and criterion for heavy work fatigue with a reaction time > 580.0 ms. The work fatigue measurement used a reaction timer because the results were measured objectively and digitally displayed, unlike the use of a questionnaire which was subjective.…”
Section: Methodsmentioning
confidence: 99%
“…The workload of a person should be appropriate and balanced. An excessively high level of workload would require a worker to use the energy excessively and lead to an overstress condition (Dwiyanti & Mustofani, 2019). On the contrary, workload which is too low would cause a worker to experience boredom or understress condition (Batubara et.al., 2021).…”
Section: Correlation Between Workload and Occurrence Of Work Accident...mentioning
confidence: 99%